Barriers and risks of Mobility-as-a-Service (MaaS) adoption in cities: A systematic review of the literature. (February 2021) - Butler, Luke; Yigitcanlar, Tan; Paz, Alexander
Abstract: There is a growing demand, across the globe, for smart mobility solutions to reduce negative social, environmental and economic externalities of private automobile travel. Mobility-as-a-Service (MaaS) is an integrated system that through a single online interface enables commuters to plan, book, and pay for trips which utilise a range of mobility providers. MaaS has a unique characteristic to provide a system into which new service options can be integrated with traditional transportation modes. This makes MaaS a potential alternative to private vehicle ownership, and a means to overcome some of the negative externalities associated with automobile dependency. To realise this potential, many cities have implemented—or are in the process of implementing—MaaS trials to better understand how this service will function within cities. This paper utilises a systematic literature review to extract insights, and develops a conceptual framework to identify barriers and risks related to MaaS adoption in cities. The study findings reveal that: (a) the desired MaaS outcomes are associated with reduced vehicle kilometres travelled, increased trip awareness, reduced parking, reduced vehicle ownership, and improved social equity; (b) MaaS supply side barriers include public private cooperation, business support, service coverage, shared vision, and data and cyber security; (c) MaaS demand side barriers are its lack of appeal to older generations, public transport users, and private vehicle users, the attractiveness of the digital platform, and user willingness-to-pay. Highlights: Barriers and risks associated with succesful implementation of Mobility-as-a-Service (MaaS) are identified. MaaS supply side barriers are lack of public private cooperation, business and political support, service coverage, vision. MaaS demand side barriers are appeal to older generations, public transport users, and private vehicle users. MaaS outcomes are reduced vehicle kilometres travelled, parking, and private vehicle ownership, and improved social equity. There is no 'one-size fit all' MaaS and consideration of local characteristics is critical for successful implementation.